Waste plastic derived nitrogen-doped reduced graphene oxide decorated core-shell nano-structured metal catalyst (WpNrGO-Pd-Ru) for a proton exchange membrane fuel cell - Dhali, Sunil; Karakoti, Manoj; Tatrari, Gaurav; Pandey, Sandeep; Rawat, Kundan Singh; Tewari, Chetna; Bhushan, Boddepalli Santhi; Jung, Yong Chae; Srivastava, Anurag; Sahoo, Nanda Gopal (Royal Society of Chemistry, 2024)
Waste plastic-derived nitrogen-doped reduced graphene oxide (WpNrGO) was demonstrated for the first time as a catalyst support for PEMFCs. WpNrGO plays a significant role in enhancing the efficacy and durability of electrocatalysts for PEMFCs. Graphene nanosheets (GNs) are obtained by upcycling waste plastic via pyrolysis, followed by the modified Hummers' method to obtain WpGO. WpNrGO was produced by the thermal annealing of WpGO with urea (NH2CONH2) at 750 °C. Further, a WpNrGO-supported palladium？ruthenium (Pd_Ru) electrocatalyst was synthesized with Pd？:？Ru concentration in the ratio 2？:？1. Synopsys-QuantumATK was used to run DFT-based first principles simulations to comprehend the ideal locations for adsorption on GNs. The resulting WpNrGO-supported Pd_Ru (2？:？1) core？shell electrocatalyst demonstrated a higher electrochemical surface area (ECSA) of ∼43 m2 g？1 for the oxygen reduction reaction (ORR) and half potential of 0.33 V, along with high catalytic activity and stability.